Metode Pendidikan Karakter Dalam Keluarga Menurut Abdullah Nashih Ulwan Dalam Kitab Tarbiyah Al Aulad Fi-Al-Islam - Ahmad Suheili (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2018)
Character education in the family which is a big responsibility that parents must give to children from an early age. This study aims to determine the method of family character education according to Abdullah Nashih Ulwan in Tarbiyah Al-Aulad Fi Al-Islam book and its relevance to the present reality. This research is a library research. The data collection was carried out using the documentation method, and Data analysis is content analysis models. The results of this study conclude that the method of character education in the family according to Abdullah Nashih Ulwan is education with exemplary, educational by habituation, education with advice, education with attention and monitoring and education with punishment. This research also concludes that the method is still relevant to the present reality.